Avaliação vestibular no recém-nascido de termo - Beuter, Cláudia Regina (2007)
A transverse study in term newborns was made to determine the occurrence of motor responses and possible asymmetries during the stimulation of the vestibular system through the head turning after release from the midline and passive rotation. From October to December of 2005, 320 neonates were admitted to the Adjacent Lodgings of the University Hospital of Santa Maria. From those, 89 were selected for assessment of the vestibular function since they have previously had fetal static control through ultrasound. Our results show that right-sided head lateralization was significantly greater than left-sided. The predominancy of the lateralization towards the right side also occurred in the male gender, cephalic presentations and left-sided back, however, not significant. On the passive rotation about the vertical axis, the great majority of the neonates presented eye deviation in the opposite direction of the body movement and about the horizontal axis, the great majority of them either remained with their eyes closed or did not present any deviation at all. Results corroborate with the existing literature and suggest an association between fetal static and vestibular function. It was shown through vestibular stimulation trials that term newborns already possess a functional asymmetry as well as motor responses to this system stimulation